2022
DOI: 10.3389/fmats.2021.804328
|View full text |Cite
|
Sign up to set email alerts
|

Active Corrosion Protection by Epoxy Coating on Li2CO3-Pretreated Anodized Aluminum Alloy 2024-T3

Abstract: The fast leaching and robust barrier property of inhibitors are the basic fundamentals for the formation of active protective coatings to protect aluminum alloys. Herein, an active protective surface was developed based on an epoxy coating and an underlying lithium carbonate (Li2CO3)-treated anodized aluminum alloy 2024-T3. The morphology of the Li-LDH layer was studied to know its formation mechanism. The electrochemical studies revealed that the fast and adequate leaching of lithium led to a substantial incr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 43 publications
(42 reference statements)
0
0
0
Order By: Relevance
“…At present, the most widely used treatment methods on aluminum alloy surfaces are anodizing and powder coating [1,[12][13][14]. Minhas Badar et al [15] developed an active protective coating surface using the rapid leaching and strong barrier properties of the corrosion inhibitor combined with the anodized aluminum alloy 2024-T3, and electrochemical studies showed that the rapid and sufficient leaching of lithium led to a significant improvement in the corrosion resistance of scratch coatings. X. H. Lin et al [16] used PEMHP (piezoelectric machine hammer peening) to study the surface modification of 6016 aluminum alloy anodizing film, including surface roughness, surface morphology, and hardness.…”
Section: Introductionmentioning
confidence: 99%
“…At present, the most widely used treatment methods on aluminum alloy surfaces are anodizing and powder coating [1,[12][13][14]. Minhas Badar et al [15] developed an active protective coating surface using the rapid leaching and strong barrier properties of the corrosion inhibitor combined with the anodized aluminum alloy 2024-T3, and electrochemical studies showed that the rapid and sufficient leaching of lithium led to a significant improvement in the corrosion resistance of scratch coatings. X. H. Lin et al [16] used PEMHP (piezoelectric machine hammer peening) to study the surface modification of 6016 aluminum alloy anodizing film, including surface roughness, surface morphology, and hardness.…”
Section: Introductionmentioning
confidence: 99%